Association Mapping in Scandinavian Winter Wheat for Yield, Plant Height, and Traits Important for Second-Generation Bioethanol Production - Bellucci, Andrea; Torp, Anna Maria; Bruun, Sander; Magid, Jakob; Andersen, Sven B.; Rasmussen, Søren K. (Frontiers in Plant Science, 2015)
A collection of 100 wheat varieties representing more than 100 years of wheat-breeding history in Scandinavia was established in order to identify marker-trait associations for plant height, grain yield and biomass potential for bioethanol production. The field-grown material showed variations in plant height from 54 to 122 cm and in grain yield from 2 to 6.61 t ha-1. The release of monomeric sugars was determined by high-throughput enzymatic treatment of ligno-cellulosic material and varied between 0.169 and 0.312 g/g dm for glucose and 0.146 and 0.283 g/g dm for xylose. As expected, plant height and grain yield showed to be highly influenced by genetic factors with repeatability (R) equal to 0.75 and 0.53 respectively, while this was reduced for glucose and xylose (R=0.09 for both) . The study of trait correlations showed how old, low-yielding, tall varieties released higher amounts of monomeric sugars after straw enzymatic hydrolysis, showing reduced recalcitrance to bioconversion compared to modern varieties. 93 lines from the collection were genotyped with the DArTseq® genotypic platform and 5525 markers were used for genome-wide association mapping. Six QTLs for grain yield, plant height and glucose released from straw were mapped. One QTL for plant height was previously reported, while the remaining QTLs constituted new genomic regions linked to trait variation. This paper is one of the first studies in wheat to identify QTLs that are important for bioethanol production based on a genome-wide association approach.